EFFORTS TO IMPROVE SCIENCE LEARNING OUTCOMES USING DEMONSTRATION METHODS - Anggita Rahmi Yunika Pratama; Hilda Wulansari; Jajang Bayu Kelana (IKIP Siliwangi, 2018)
The main problem is science from elementary school students in West Bandung Regency. This is a program that is used to improve students' abilities in the west Bandung district elementary school. In particular, the targets to be mentioned are as follows: 1) Improve student learning achievement after the implementation of the demonstration method 2) Can affect student learning after the demonstration method is applied. The method that will be used is a method of observation with the material properties of light in class V elementary schools in West Bandung regency precisely at SDN Nugraha. The method used is qualitative with a classroom action research approach (CAR). The subject of the research was the fifth grade students of Nugraha Elementary School with 28 students.